2023
DOI: 10.3389/fonc.2023.1148930
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional heterotypic colorectal cancer spheroid models for evaluation of drug response

Abstract: Colorectal cancer (CRC) is a leading cause of death worldwide. Improved preclinical tumor models are needed to make treatment screening clinically relevant and address disease mortality. Advancements in 3D cell culture have enabled a greater recapitulation of the architecture and heterogeneity of the tumor microenvironment (TME). This has enhanced their pathophysiological relevance and enabled more accurate predictions of tumor progression and drug response in patients. An increasing number of 3D CRC spheroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Cancer spheroids have been used as a threedimensional (3D) tumor tissue model expressing tumor growth for drug screening. 106,107 Colon26 spheroids in the active growing phase were exposed to CB@EVs, CB@ liposome, and the L-BPA/fructose complex (0.1 ppm) and irradiated with a thermal neutron at KUR. BNCT activity was monitored at 1, 2, and 7 days postirradiation by the WST-8 assay.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Cancer spheroids have been used as a threedimensional (3D) tumor tissue model expressing tumor growth for drug screening. 106,107 Colon26 spheroids in the active growing phase were exposed to CB@EVs, CB@ liposome, and the L-BPA/fructose complex (0.1 ppm) and irradiated with a thermal neutron at KUR. BNCT activity was monitored at 1, 2, and 7 days postirradiation by the WST-8 assay.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…One of the main advantages of using spheroids in cancer research is the ability to measure drug response. Multiple studies have been conducted involving spheroids derived from various types of cancer, including colorectal cancer [ 39 , 40 , 41 , 42 ], breast cancer [ 41 , 43 , 44 ], lung cancer [ 45 , 46 ], ovarian cancer [ 1 , 47 , 48 ] and even Ewing sarcoma cells [ 49 ]. It is important to note that 3D cultures, particularly spheroids, are a valuable and effective tool for studying cancer biology.…”
Section: 3d Cell Culturesmentioning
confidence: 99%
“…We previously found that depending on the specific in vitro microenvironmental condition, cancer cells display different chemoresistance profiles. For instance, cells growing under adherent conditions are more sensitive compared to cells growing under suspension conditions [ 2 4 ]. On the other hand, cells growing in the absence of serum are more resistant compared to cells growing in the presence of serum [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%